CURRICULUM INTEGRATION OF POPULATION MATERIALS IN SCIENCE SUBJECTS AT SENIOR HIGH SCHOOL - Wartiningsih, Wartiningsih; Muhtadi, Ali (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
Various population issues become challenges in sustainable development in Indonesia. For this reason, synergy from various parties is needed to overcome and anticipate the problems caused by this population impact. One of them is by increasing the strategic role of teachers in instilling knowledge, attitudes, behaviors that are responsive and adaptive in dealing with population situations for headmaster, educators, education staff, and students. The effort that can be done is to integrate population material into the teaching and learning process according to the curriculum and local culture. The purpose of the study was to find out the implementation of the population material integration curriculum at High School. The results of this study are that the school curriculum can integrate population material with science subjects, but must be supported by teachers, students, headmaster. In conclusion, the school curriculum at the high school level can be integrated with population material with support from various parties.